Global research trends of diabetes remission: a bibliometric study - Yang, Xue; He, Zhiwei; Chen, Qilin; Chen, Yu; Chen, Guofang; Liu, Chao (Frontiers in Endocrinology, 2023)
Background: Research on diabetes remission has garnered prominence in recent years. However, to date, no pertinent bibliometric study has been published. This study sought to elucidate the current landscape and pinpoint potential new research directions through a bibliometric analysis of diabetes remission. Methods: We perused relevant articles on diabetes remission from January 1, 2000, to April 16, 2023, in the Web of Science. We utilized CiteSpace software and VOSviewer software to construct knowledge maps and undertake analysis of countries, institutional affiliations, author contributions, journals, and keywords. This analysis facilitated the identification of current research foci and forecasting future trends. Results: A total of 970 English articles were procured, and the annual publication volume manifested a steady growth trend. Most of the articles originated from America (n=342, 35.26%), succeeded by China and England. Pertaining to institutions, the University of Newcastle in England proliferated the most articles (n=36, 3.71%). Taylor R authored the most articles (n=35, 3.61%), and his articles were also the most co-cited (n=1756 times). Obesity Surgery dominated in terms of published articles (n=81, 8.35 %). “Bariatric surgery” was the most prevalently used keyword. The keyword-clustering map revealed that the research predominantly centered on diabetes remission, type 1 diabetes, bariatric surgery, and lifestyle interventions. The keyword emergence and keyword time-zone maps depicted hotspots and shifts in the domain of diabetes remission. Initially, the hotspots were primarily fundamental experiments probing the feasibilities and mechanisms of diabetes remission, such as transplantation. Over the course, the research trajectory transitioned from basic to clinical concerning diabetes remission through bariatric surgery, lifestyle interventions, and alternative strategies. Conclusion: Over the preceding 20 years, the domain of diabetes remission has flourished globally. Bariatric surgery and lifestyle interventions bestow unique advantages for diabetes remission. Via the maps, the developmental milieu, research foci, and avant-garde trends in this domain are cogently portrayed, offering guidance for scholars.